Soccer - Hornby, Hugh (DK eyewitness books., 2018)
Describes the game of soccer around the world from its origins to the recent World Cup finals. Focuses on its history, rules, refereeing, the field, and soccer skills. Includes data on the goalkeeper, strategies, and equipment as well as accessories. Concludes with information on famous players, cups, trophies, and soccer as a business.